212k views
3 votes
F ( x ) = 3x + 2 and g ( x ) = 2x – 5 find f ( 2 ) + g ( 1 )

1 Answer

6 votes

Answer:

Given:

f(x) = 3x + 2

g(x) = 2x – 5

f(2)+g(1)

----------------------------------------------------------------

Above we have three clues that we got from the question.

First, substitute the value of f(2) for f(x)

3(2)+2

6+2

8

Second, substitute the value of g(1) for g(x)

2(1)-5

2-5

-3

Now we have to add the f(x) value which is 8 and the g(x) value which is -3.

8+-3

5

Your final answer would be 5.

User Zimmer
by
6.4k points